2019
DOI: 10.3390/c5030040
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Plasma-Treated Carbon Nanowalls’ Surface-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (CNW-SALDI-MS)

Abstract: Carbon nanowalls (CNWs), vertically standing highly crystallizing graphene sheets, were used in the application of a surface-assisted laser desorption/ionization time-of-flight mass spectrometry (SALDI-TOF-MS). The CNW substrates solved the issues on interferences of matrix molecules and alkali metal addition ions in low-weight molecule detection. Before SALDI sample preparations, the hydrophobic CNW was treated by atmospheric pressure plasma for exposing hydrophilicity to the CNWs’ surface. Detection of water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…[Arg + H] + signals were clearly observed in all spectra, regardless of the wall-to-wall distances of the CNWs [35]. Signals corresponding to fragment ions of arginine also appeared at 160, 130, 124, 116, 114, and 112 [32]. The fragment ions of arginine, m/z = 112 and 116, were assigned to [Arg + H-NH 3 -HCOOH] + (or [C 5 H 10 N 3 ] + ) and [Arg + H-CH 5 N 3 ] + (or [C 5 H 10 NO 2 ] + ), respectively [32,36].…”
Section: N-bp-cl Detectionmentioning
confidence: 89%
See 3 more Smart Citations
“…[Arg + H] + signals were clearly observed in all spectra, regardless of the wall-to-wall distances of the CNWs [35]. Signals corresponding to fragment ions of arginine also appeared at 160, 130, 124, 116, 114, and 112 [32]. The fragment ions of arginine, m/z = 112 and 116, were assigned to [Arg + H-NH 3 -HCOOH] + (or [C 5 H 10 N 3 ] + ) and [Arg + H-CH 5 N 3 ] + (or [C 5 H 10 NO 2 ] + ), respectively [32,36].…”
Section: N-bp-cl Detectionmentioning
confidence: 89%
“…A time-of-flight mass spectrometer system (TOF-MS; Toyama Co., Ltd., Kanagawa, Japan) was used in this experiment [32]. The background pressures of the ionization chamber and the TOF chamber were kept below 10 −7 Pa.…”
Section: Saldi-tof-ms Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface Modifications at Ambient Conditions : The high energy electrons, radicals, and reactive species generated in the microplasma can be used for surface modification of materials. It has been reported that the surface properties of CNMs, polymeric films, can be modified by microplasmas‐based treatments. The plasma modification step can further change the optical, electronic, and other properties of materials.…”
Section: Production Of Advanced Nanomaterialsmentioning
confidence: 99%